2012
DOI: 10.1007/s13238-012-2082-x
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of Lamellipodin implicates diverse functions in actin polymerization and Ras signaling

Abstract: The adapter protein Lamellipodin (Lpd) plays an important role in cell migration. In particular, Lpd mediates lamellipodia formation by regulating actin dynamics via interacting with Ena/VASP proteins. Its RA-PH tandem domain confi guration suggests that like its paralog RIAM, Lpd may also mediate particular Ras GTPase signaling. We determined the crystal structures of the Lpd RA-PH domains alone and with an N-terminal coiled-coil region (cc-RA-PH). These structures reveal that apart from the anticipated coile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 26 publications
1
18
0
Order By: Relevance
“…The overall structure of the complex is shown in Figure 1A. As first observed in the Grb10 RA-PH structure [12], and more recently in the RIAM [17] and lamellipodin [19] RA-PH structures, the RA and PH domains of Grb14, together with the intervening linker of ~40 residues, share an extensive interaction interface, which creates an integrated two-domain structural unit. The four copies of Grb14 RA-PH -Ras in the asymmetric unit are highly similar and superimpose on one another with a root-mean-square deviation (rmsd) of <1 Å (410 Cα atoms).…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…The overall structure of the complex is shown in Figure 1A. As first observed in the Grb10 RA-PH structure [12], and more recently in the RIAM [17] and lamellipodin [19] RA-PH structures, the RA and PH domains of Grb14, together with the intervening linker of ~40 residues, share an extensive interaction interface, which creates an integrated two-domain structural unit. The four copies of Grb14 RA-PH -Ras in the asymmetric unit are highly similar and superimpose on one another with a root-mean-square deviation (rmsd) of <1 Å (410 Cα atoms).…”
Section: Resultsmentioning
confidence: 74%
“…The PH domain adopts the canonical PH-domain fold [21], comprising a seven-stranded β sheet and a C-terminal α helix. An additional helix follows on the C-terminal end, which is also present in the Grb10 [12], RIAM [17], and lamellipodin [22] RA-PH structures. In the Grb10 RA-PH structure, this extra helix mediates RA-PH dimerization [12], but it is not observed to do so in the Grb14 RA-PH structure, although that does not necessarily preclude a dimerization role for this helix in vivo .…”
Section: Resultsmentioning
confidence: 99%
“…This observation reveals that small lamellipodin puncta are precursors to larger VASP/lamellipodin clusters that concentrate at the tips of nascent filopodia bundles and raises the question of how small lamellipodin puncta form in the first place. Two possibilities are: (i) lamellipodin can independently form small homo-oligomers, which is supported by a structural study that identified two dimerization motifs at its N-terminal RAPH domain (Chang et al 2013) and (ii) lamellipodin foci mark the position of larger complexes that contain other, as yet unidentified proteins.…”
Section: Discussionmentioning
confidence: 97%
“…The Ena/VASP Homology-1 (EVH1) domain of VASP helps determine its subcellular localization by binding proteins that contain an FPPPP (or less commonly LPPPP) motif, such as zyxin, vinculin, Abi1, RIAM, and lamellipodin (Ball et al 2000;Lafuente et al 2004;Brindle et al 1996;Reinhard et al 1996;Gertler et al 1996;Prehoda et al 1999; Krause et al 2004;Bear et al 2000;Niebuhr et al 1997) . Using purified proteins and in vitro assays we previously found that lamellipodin, which contains six F/LPPPP motifs and forms membrane-associated dimers (Chang et al 2013) , can co-cluster with VASP on actin filaments (Hansen and Mullins 2015) . We also found that clusters of purified lamellipodin recruit VASP and dramatically increase the processivity of its actin polymerase activity.…”
Section: Introductionmentioning
confidence: 99%
“…The PH domain-containing protein lamellipodin (Lpd), also known as Ras association and PH domains 1, is proposed to be a specific PI(3,4)P2-binding protein (29)(30)(31)(32); however, one dissenting study proposed that its PH domain might not be effective in PI binding (33). Lpd was shown to mediate random motility in breast cancer cells (29,34) as well as extension of neuronal processes (35).…”
mentioning
confidence: 99%